Training load and performance in swimming - Chatard, J. -C.; Stewart, A. M. (World book of swimming: From science to performance, 2012)
More than three quarters of all competitive swimming events are completed in less than two and a half minutes by athletes of at least national class. To prepare for these events, coaches manipulate training load (usually described as a combination of volume, intensity, frequency, and dry-land training) at various times of the scason in an attempt to prepare their swimmers to peak just at the right time. Leading into competition, there is usually a phase of high load training followed by some kind of tapering (reduced load) program. Scientific data support bigger performance gains through a program based on high intensity and low volume prior to a high-load phase and taper phase leading into compctition. Individual athletes will respond differently to such fluctuations in training load and will depend on parameters such as training status at the time and performance Ievel. Individual responses can be monitored using simple observational or monitoring techniques, regression analysis, or with the help of a systems model. These analytical proccsses may be useful tools to establish individualized training programs.